The marvelous thing that came from a spring : the accidental invention of the toy that swept the nation - Ford, Gilbert (Atheneum Books for Young Readers, 2016)
"With magnificent dioramic illustrations, Gilbert Ford captures the joy, creativity, and determination behind the invention of an iconic, one-of-a-kind toy: the Slinky! One day, a spring fell from the desk of Richard James, an engineer and a dreamer. Its coils took a walk ... and so did Richard's imagination. He knew right away that he had stumbled onto something marvelous. With the help of his wife, Betty, Richard took this ordinary spring and turned it into a plaything. But it wasn't just any old trinket--it was a Slinky, and it would become one of the most popular toys in American history, "--Amazon.com.